GAMBARAN PELAKSANAAN PATIENT SAFETY OLEH PERAWAT INSTALASI BEDAH SENTRAL RSUP DR SARDJITOYOGYAKARTA - heru Sriyana; Maria H Bakri; Sugeng Sugeng (Jurnal Kesehatan Karya Husada, 2014)
Background: The WHO estimates that half a million deaths caused by surgery that should be preventable through patient safety programme. Indonesia has also issued Kepmenkes guidelines of medical audit for hospital to acvieve medical services far from medical error. Dr. Sardjito General Hospital formed patient safety team and clinical risk management. Whiser research (2008) represent the surgical patient safety reduced ILO from 11.2 to 6.6. ILO in Dr. Sardjito General Hospital in 2012 amount of 0.13%. Dr. Sardjito General Hospital nurses are not consistent on sign in, time out and sign out phase. Objective: To determine the implementation of patient safety programme in the central surgical installation of Dr. Sardjito General Hospital Yogyakarta. Methods: The research was descriptive and cross-sectional design. Research performed at the Central Surgical Installation of Dr. Sardjito General Hospital Yogyakarta. Subjects were all nurses perioperative in Central Surgical Installation of Dr. Sardjito General Hospital Yogyakarta on the 4th floor and 5th floor as many as 39 people. Research instruments using observation sheets and the data were analyzed descriptively and presented in tabular form. Results: Nurses in Central Surgical Installation of Dr. Sardjito General Hospital Yogyakarta majority aged young adults (64.1%), DIII educated nursing (79.5%), and have a service life e” 3 years (89.7%). Sign in implementation by the majority of nurses in both categories (87.2%), the majority of the execution time out in both categories (89.7%), and the sign out the implementation of the majority in both categories (92.3%). Conclusions: The implementation of patient safety programme by nurses in Central Surgical Installation of Dr. Sardjito General Hospital Yogyakarta majority are good